Three-dimensional analysis of geosynthetic-encased granular columns for liquefaction mitigation. Issue 1 (1st August 2016) - Geng, L.; Tang, L.; Cong, S. Y.; Ling, X. Z.; Lu, J.
Abstract : Extensive numerical and experimental studies have been conducted to investigate the behavior of soft ground improved with geosynthetic-encased stone columns (ESCs). However, almost no studies have been performed to evaluate the use of ESC in mitigating the liquefaction hazard of saturated sand strata. For this purpose, three-dimensional nonlinear finite element (FE) analyses using the open-source computational platform OpenSees was performed to evaluate the mitigation of mildly sloping saturated cohesionless strata improved with the ESCs. A systematic parametric study was conducted to investigate the potential influence of geosynthetic/encasement length ( L enc ), soft clay interlayer, and ground motion characteristics on improved efficiency. ESC remediation in various types of sand strata is also addressed. In addition, the effect of ground slope angle on the deployed remediation is discussed. Generally, ESC remediation was observed to be effective in reducing lateral deformation of the sand strata. It was found that improved efficiency also seemed to be definitely influenced by the geosynthetic/encasement length L enc, the various types of sand strata, the thickness of the soft clay interlayers, and ground motion characteristics. Overall, ESC remediation may be used to achieve a reliable solution through the provided approaches.